Development of wave technology as an energy efficiency mechanism in Ecuador: Esmeraldas case study (Revista Repique, 2023)
In recent years, technologies based on the use of renewable alternative energies have been incorporated into different activities in productive sectors, becoming a viable alternative to reduce energy consumption and contribute to the environmental impact, generating clean and non-polluting energies; one of them being wave energy, which takes advantage of the movement of the waves to receive and retain the energy contained in them, transforming it through electromagnetic induction processes into electrical energy. For this reason, it was proposed in this research to develop a proposal for the development of wave energy technology as a mechanism for energy efficiency in the coastal area of the canton of Esmeraldas, Ecuador. For this purpose, a study based on applied research was established because it is based on solving a specific problem or specific approach, focusing on the search and consolidation of knowledge for its application and, therefore, for the enrichment of cultural and scientific development. Among the conclusions identified during the analysis of the energy potential of waves, it was found that there are favorable results in the canton of Esmeraldas as a possible means of generating alternative energy from the sea, presenting the necessary environmental parameters for capturing energy from wave characteristics such as the average annual wave height, the constant period of the wave, the density of sea water and the average speed, being a sustainable alternative for the supply of electricity in the coastal area of the canton of Esmeraldas, Ecuador.